PENGEMBANGAN KAWASAN EKOWISATA DI KECAMATAN MEMPURA KABUPATEN SIAK - sufi, wasiah; nurpeni, nurpeni; sari, fara merian (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
Siak Regency is one of the areas in Riau that has the potential to develop tourism in the region, precisely in Kecamatan Mempura include: natural potential, historical potential, socio-cultural potential, and the potential of agriculture and condensation. They are: Tangsi Belanda, Tomb of Sultan Buang Asmara, Kotler House and Office, Datuk Pesisir House, Dome of the Dome, Wedana Office at Lower Hilir. The tourism sector requires a good development of tourism. The potentials that are owned can be developed and get maximum results. From the explanation the authors use descriptive research type using qualitative research methods with the focus of research 1.Policy Ecotourism development in Siak District 2. obstacles in ecotourism development in Kecamatan Mempura Siak regency. The research results explained that the development of ecotourism area in Districk Mempura is still not yet Maximum because there are still many obstacles faced by local government Mempura